Skenario Pengembangan Produksi Lapangan “NATA” dengan Software Integrated Production Modelling - Lia Yunita; Heru Danardatu; Endro Tegar Prakoso (Jurnal Migasian, 2025)
Integrated production modeling (IPM) is a software for modeling oil and gas production systems from reservoirs, wells and surface networks. IPM consists of GAP, PROSPER, MBAL, PVTP, REVEAL and RESPLVE. The purpose of the study is to plan the development scenario of the "NATA" field using IPM. The "NATA" field has nine wells and three productive zones, namely N-1, N-2 and N-3. The method used is modeling from the reservoir using MBAL software, followed by well modeling using Prosper Software, then in the final stage is to design the surface facilities of the "NATA" field using GAP Software. The results of running for 10 years until 2034 obtained reservoir N-1 produced by three wells obtained with reservoir pressure 1560 psig, oil production 1500 STB / day liquid production 1600 STB / day, water production 108 STB / day. In reservoir N-2, one well was produced, reservoir pressure 1300 psig, oil production 850 STB/day, liquid production 890 STB/day, water production 21 STB/day were obtained. In reservoir N-3, five wells were produced, reservoir pressure 1860 psig, oil production 100 STB/day, liquid production 200 STB/day, water production 100 STB/day were obtained. The development scenario of the "NATA" field with IPM until 2035 obtained a reservoir that is prospective to be developed, namely reservoir N-1 which still has a high production rate.